Remain of a Dialect in an Urban Cultural Medium by Means of Folk-tales: Role of Some Tale-tellers of a Hungarian Ethnic Group Székelys of Bukovina in Hungary - Pal, Helen (Ethnographica et Folkloristica Carpathica, 2022)
The aim of the paper is to show the role that storytellers can play in the transmission of traditions, identity and dialect today. The paper focuses on a Hungarian ethnic group: Szeklers of Bukovina settled in Hungary in 1945. The main aim of this paper is to present the function of dialects in tales and tale-telling after the change of traditional peasant way of life and dialects. In Bukovina this ethnic group was isolated from the Hungarian mother-country and the majority of Hungarians, their cultural and language changes did not reach them, therefore the members of this ethnic group could retain their traditional culture and dialect. However, in Hungary they were settled into 38 settlements, thereby their original communities broke up. The dialectal and sociolinguistic data of this paper comes from the storyteller’s websites, written and oral personal stories, the text and sound-recording of folk-tales, and also data of formal dialectal researches of this ethnic group is used. This paper presents an analysis of some storytellers who use several dialect elements of this ethnic group, besides the role of dialects in tale-telling is studied too. It is an important aspect of this analyse how some storytellers utilize their dialect in tales and during tale-telling, and why they usually use it. The results of research present that these storytellers can use dialect elements in different ways in their tale-telling. The main conclusion is that use of a dialect can be a part of language education, a dialect is an identity marker, and by the help of it a storyteller can create a pictorial experience during the tale-telling, besides it can be a source of humour too.